STUDENTS' PERCEPTIONS OF DIGITAL MEMES IN LEARNING ENGLISH VOCABULARY: A CASE STUDY OF EIGHTH-GRADE STUDENTS - Wahdatul Alawiah, Siti; Hidayani, Selnistia; Oktaviana, Fadilla (Universitas Tanjungpura, 2026)
This study explores eighth-grade students’ perceptions of using digital memes in learning English vocabulary within an EFL context. Employing a qualitative case study design, the research involved seven junior high school students selected through purposive sampling. Data were collected via semi-structured interviews and analyzed thematically with the support of NVivo software to capture the cognitive, affective, and behavioral dimensions of students’ learning experiences. The findings indicate that digital memes enhance motivation, engagement, and vocabulary retention by promoting contextualized understanding through visual and humorous elements. Additionally, memes contribute to a relaxed learning environment that reduces anxiety and encourages active participation and peer interaction. Nevertheless, challenges emerged in interpreting idiomatic expressions and culturally specific references, underscoring the importance of teacher guidance in meme selection and explanation. Overall, digital memes demonstrate strong pedagogical potential as multimodal resources in EFL vocabulary instruction at the junior high school level.